Raising interest rates for improving income - Guillermo Pe\~na (Journal of Central Banking Theory and Practice, 2023)
This paper illustrates a case where an increase of the in-terest rates improves the economic activity and reduces incomeinequality. This theoretical exercise deals with a simple model ofdisequilibrium with accountant identities of budget constraints. Inaddition, and following previous models, the effect of the COVID-19shock is considered, by reflecting asymmetric repercussions that in-crease income inequality. A simple empirical exercise confirms someof the previous results. The proposed explanation is that, for the euroarea, this shock has affected more middle-income households suchas the retailers harmed by the compulsory lockdown who have in-creased their debts.
Keywords: E52; E25; E58; G21; 330; Monetary policy; Income inequality; Financial sector; Black Swan; COVID-19; Unemployment